The epidemiology and burden of Alzheimer’s disease in Taiwan utilizing data from the National Health Insurance Research Database - Hung YN; Kadziola Z; Brnabic AJM; Yeh JF; Fuh JL; Hwang JP; Montgomery W (Dove Medical Press, 2016)
Yen-Ni Hung,1 Zbigniew Kadziola,2 Alan JM Brnabic,3 Ju-Fen Yeh,4 Jong-Ling Fuh,5,6 Jen-Ping Hwang,7,8 William Montgomery,9 1School of Gerontology Health Management and Master Program in Long-Term Care, College of Nursing, Taipei Medical University, Taipei, Taiwan, Republic of China; 2Real World Analytics, Eli Lilly GmbH, Vienna, Austria; 3Real World Analytics, Eli Lilly Australia Pty Ltd, West Ryde, NSW, Australia; 4Department of Medicine, Eli Lilly and Company, Taiwan, Republic of China; 5Department of Neurology, Neurological Institute, Taipei Veterans General Hospital, 6Faculty of Medicine, School of Medicine, National Yang Ming University, 7Department of Psychiatry, Taipei Veterans General Hospital, 8Division of Psychiatry, School of Medicine, National Yang-Ming University, Taipei, Taiwan, Republic of China; 9Eli Lilly Australia Pty Ltd, West Ryde, NSW, Australia Purpose: The objectives of this study were to estimate the incidence, cumulative incidence, and economic burden of Alzheimer’s disease (AD) in Taiwan, using data from the National Health Insurance Research Database (NHIRD).Materials and methods: This was a retrospective, longitudinal, observational study using data from the Longitudinal Health Insurance Database of the NHIRD. Patients were included in this study if they were 50 years of age or older and their records included a primary or secondary diagnosis of AD. New patients who met inclusion criteria were followed up longitudinally from 2005 to 2010. Costs were calculated for the first year following the diagnosis of AD.Results: Overall, a higher percentage of women than men were diagnosed with AD (54% vs 46%, respectively). The first AD diagnosis occurred most frequently in the age of 75–84 years. The person-year incidence rate increased from 5.63/1,000 persons (95% CI, 5.32–5.94) in 2005 to 8.17/1,000 persons (95% CI, 7.78–8.57) in 2010. The cumulative incidence rate was 33.54/1,000 persons (95% CI, 32.76–34.33) in 2005–2010. The total mean inflated annual costs per patient in new Taiwan dollars (NT$) in the first year of diagnosis ranged from NT$205,413 (2009) to NT$227,110 (2005), with hospitalization representing the largest component.Conclusion: AD represents a substantial burden in Taiwan, and based on the observed increase in incidence rate over time, it is likely that this burden will continue to increase. The findings reported here are consistent with previous research. The NHIRD contains extensive real-world information that can be used to conduct research, allowing us to expand our understanding of the incidence, prevalence, and burden of disease in Taiwan. Keywords: Alzheimer’s disease, incidence, medical costs, resource utilization